Evaluasi Kinerja Park And Ride Di GAmping Yogyakarta (Studi Kasus Halte Park And Ride Trans Jogja Ambarketawang Gamping) - Ahmad Abdul Rosyid Ridho,; Ani Tjitra Handayani,; Herna Puji Astutik , (ReTII, 2023)
Park and Ride plays a role as a driver and effort to increase the role of mass public transportation in the city of Yogyakarta, overcome congestion and reduce the useof earth’s energy and reduce existing air pollution. The importance of the transportation service sector needs to be supported by a fairly good service quality by service providers. Therefore this research was conducted to determine the performance and quality of service and facilities availabe at the Park and Ride in Gamping Yogyakarta. The research method used in this research is descriptive method. Descriptive method of analysis by analyzing the data that has beencollected, grouped, analyzed, so that a clear picture is obtained abaout how the performance, faculities and satisfaction of service users with the received. Based on the results of the questionnaire data analysis using the IPA method (Importance Performance Analysis), the result is that the average score levels score is 1178,6 and the satisfaction level is 1181,4, which mean that overall the quality of the service provided is satisfactory for service users, then for the parking capacity obtained 2,796 per hour, for the analysis of the waiting room obtained an area of 490 m2 and for the analysis of the transport area (load factor) obtained 22,657% < 100% for incoming passengers and 22,857% < 100% for outgoing passengers, it can be stated that the load factor meets the standart of trasport capacity.